Southwest Research-Extension Center Field Day 2014 (Kansas Agricultural Experiment Station Research Reports, 2014)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: crops; tillage; soil fertility; weed science; irrigation; SRP1104; 2014